Analysis Of Ergonomic Lecturer Work Chair Design With Anthropometric Method - Trisolvena, Nana (Greenation Research & Yayasan Global Resarch National, 2023)
Ergonomic lecturer chairs following the dimensions of the lecturer's body need to be designed so that lecturers can be healthy and comfortable in carrying out the duties of education, research, and community service. Body dimensions that can be used to design lecturer chairs are upright sitting height (TDT), front hand reach (JTD), shoulder width (LB), and hand length (PT). The research was conducted to analyze lecturer complaints during work and design ergonomic work chairs. The method used in this study is the anthropometric method. The results showed that the most complaints on the neck, shoulders, legs (calves), and ankles were 15.58% respectively followed by knees 11, 69%, and thighs 7.79%. From the measurement of the body, dimensions obtained ? TDT 84 cm, ? 3,117; ? JDT 69.5 cm, ? 4.89; ? LB 42.75 cm, ? 2.915 and ? PT 40.86 cm, ? 4.357 with normally distributed data. 5th percentile TDT 80 cm, 50th TDT 84 cm, 95th TDT 90.65 cm. 5th percentile JTD 63.15 cm, le-50 JTD 72 cm, 95th KTD 77.85 cm. 5th percentile LB 38.9 cm, 50th LB 43.5 cm and 95th LB 47 cm. 5th percentile PT 34.9 cm, 50th PT 43 cm and 95th PT 16.55 cm. The conclusion of designing ergonomic lecturer chairs is following the percentile value obtained using body dimensions.